Profil Psikografis & Penggunaan Media pada Kelompok Milenial Pengunjung Kebun Binatang Surabaya - Anak Agung Istri Satvikadewi; Herlina Kusumaningrum (LPPM Stikosa - AWS, 2019)
This study describes the psychographic profile and the use of media by the visitors of the Surabaya Zoo from the millennial age group, which is between 19 s.d. 40 years old. This age generation is the result of demographic bonuses for groups or generations born between the 1980s and 2000s, with characteristics that reflect the transition between the previous generation (baby boomers) and afterwards (gene Z) in terms of lifestyle and media use. This difference is partly due to a shift in communication technology that also affects their media consumption patterns. The characteristics of millennials are identified by special behavior, being protected, confident, group oriented, conventional, resistant to pressure and pursuing achievement. Surabaya Zoo which is a local tourism destination that is officially managed by the Surabaya City Government is required to contribute to the local revenue of the City of Surabaya. The breakthrough that has been done targeting the Millennial generation that tends to be individually oriented is to provide a Selfie park and offer activities that attract the interest of visitors. This program has increased the number of KBS visitors from year to year. By employing survey methods and measuring VALS (Values And Life Style) and frequency of media use by respondents, the results obtained that the psychographic profile of KBS visitors can be categorized tend to be Principle Oriented, whose lifestyle is characterized by: having spiritual values, not thinking about prestige, like learning something new, have a traditional mindset, and do a fixed routine for a long time. With this profile, the main expectation of millennial for the availability of information at the Surabaya Zoo is information about animals, instead of the need for selfies.Keywords: psychographic profile, millennial, media use